Intergenerational earnings mobility in Japan among sons and daughters: Levels and trends - Arnaud Lefranc; Fumiaki Ojima; Takashi Yoshida (Institute for the Study of Labor (IZA), 2012)
This paper estimates the extent of intergenerational income mobility in Japan among sons and daughters born between 1935 and 1975. Our estimates rely on a two-sample instrumental variables approach using representative data from the Japanese Social Stratification and Mobility (SSM) surveys, collected between 1965 and 2005. Father's income is predicted on the basis of a rich set of variables including education, occupation and job characteristics and we discuss changes in the Japanese earnings structure for cohorts born between the early 1900s and the 1960s. Our main results indicate that the intergenerational income elasticity (IGE) for both sons and daughters, in Japan lies around .35, which is an intermediate value, by international standards. We discuss the sensitivity of the IGE to using either personal or family income as the income variable for both fathers and children and perform some robustness analysis with respect to the first-step specification and to the age selection rule for children. We also examine changes across cohorts in the IGE. Results indicate that intergenerational mobility has been roughly stable over the last decades. Lastly, we estimate the intergenerational correlation of earnings.
Keywords: D1; D3; J3; 330; intergenerational mobility; elasticity; correlation; earnings differentials; income; inequality; trends; Japan; assortative mating; education; Einkommen; Einkommenselastizität; Generationenbeziehungen; Soziale Mobilität; Schätzung; Japan